2020
DOI: 10.1146/annurev-immunol-071219-125715
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Metabolites in Health and Disease

Abstract: Metabolism is one of the strongest drivers of interkingdom interactions—including those between microorganisms and their multicellular hosts. Traditionally thought to fuel energy requirements and provide building blocks for biosynthetic pathways, metabolism is now appreciated for its role in providing metabolites, small-molecule intermediates generated from metabolic processes, to perform various regulatory functions to mediate symbiotic relationships between microbes and their hosts. Here, we review recent ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
125
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(134 citation statements)
references
References 199 publications
1
125
0
Order By: Relevance
“…39,40 Interestingly, these compounds are also used for interkingdom communication, and examples of microbe-host interactions that occur through small molecules and signaling mechanisms continue to be reported. [41][42][43][44] Recently, Uchimura et al demonstrated that there is an extensive penetration of a broad range of bacterial small molecules into host tissues, suggesting that the effects of microbial compounds on host physiology are likely to be much larger than currently appreciated. 7 Using metabolomics, we have previously shown that the human gut is teeming with small molecules, and that many of the molecules detected may represent new compounds.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 Interestingly, these compounds are also used for interkingdom communication, and examples of microbe-host interactions that occur through small molecules and signaling mechanisms continue to be reported. [41][42][43][44] Recently, Uchimura et al demonstrated that there is an extensive penetration of a broad range of bacterial small molecules into host tissues, suggesting that the effects of microbial compounds on host physiology are likely to be much larger than currently appreciated. 7 Using metabolomics, we have previously shown that the human gut is teeming with small molecules, and that many of the molecules detected may represent new compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, gut health was mainly assessed through histological observations. The development of 16S RNA based on high throughput sequencing techniques has enabled the precise detection of complex microbial communities in animals gastrointestinal tract (GIT), named microbiota, which has been closely linked not only to digestion but also to immunity and resistance of the animals to diseases (Egerton et al, 2018;Kayama et al, 2020;McCarville et al, 2020). Diet composition is recognised as one of the major factors affecting this gut microbiota and dietary insects may subsequently modulate the gut microbiota of the animals feeding on these insects (Vogel et al, 2018).…”
Section: Microbiota Modulation and Gut Healthmentioning
confidence: 99%
“…Regarding cancer, many microbial metabolites have been classified as carcinogenic, with three main mechanisms by which they affect tumor development: (1) promotion of DNA damage; (2) immune system modulation; or (3) alteration of metabolite availability (Figure 2). In addition to circulating metabolites from the gut microbiota [137], microbes that reside within tumors of other organs are able to synthesize a multitude of metabolites. However, the vast majority of studied mechanisms have been in the context of the gut microbiome and CRC development.…”
Section: Contribution Of the Intratumoral Microbiota To Carcinogenesismentioning
confidence: 99%